Correlation Between Serum Ferritin Levels and Hematological Parameters in Iron Deficiency Anemia. A Clinical Study - Nabeela Yasmeen, Khawar Younas, Bakhtawar Farooq, Umair Khan Sherwani, Ubaid Ullah Ansari, Ejaz Hussain Sahu (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Iron deficiency anemia (IDA) remains one of the most prevalent nutritional disorders worldwide, particularly in developing countries. Serum ferritin is widely recognized as the most specific biochemical marker for assessing iron stores, whereas hematological indices provide valuable information about red cell morphology and anemia severity. Understanding the correlation between these parameters can improve the diagnostic accuracy and management of IDA. Objective: To evaluate the correlation between serum ferritin levels and hematological parameters among patients diagnosed with iron deficiency anemia. Methods: This cross-sectional clinical study was conducted at the Department of Pathology, Multan Medical and Dental College, Multan, from March 2022 to March 2023. A total of 120 patients aged 18–60 years with clinically and laboratory-confirmed IDA were included. Hematological parameters including hemoglobin (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), and red cell distribution width (RDW) were measured using an automated hematology analyzer (Sysmex XN-1000). Serum ferritin was estimated using an enzyme-linked immunosorbent assay (ELISA). Data were analyzed using SPSS version 25.0, and correlations were determined using Pearson’s correlation coefficient (r). A p-value < 0.05 was considered statistically significant. Results: The mean serum ferritin level was 17.5 ± 6.8 ng/mL, and the mean hemoglobin concentration was 9.2 ± 1.4 g/dL. Serum ferritin showed a strong positive correlation with hemoglobin (r = +0.79, p < 0.001), MCV (r = +0.66, p < 0.001), MCH (r = +0.59, p < 0.01), and MCHC (r = +0.47, p < 0.05), while RDW demonstrated a significant negative correlation (r = –0.64, p < 0.001). These findings indicate that decreasing ferritin levels are associated with worsening anemia and increased red cell size variability. Conclusion: Serum ferritin levels exhibit a strong positive correlation with hemoglobin and red cell indices and a negative correlation with RDW in patients with iron deficiency anemia. The combined evaluation of ferritin and hematological parameters provides an effective and economical approach for diagnosing and monitoring iron deficiency anemia in clinical practice. Keywords: Iron Deficiency Anemia, Serum Ferritin, Hemoglobin, Red Cell Indices, MCV, RDW, Correlation Study.